INFLUENCE EXCELENT SERVICE LOYALTY SAVING AT BMT MEMBER MARDHATILLAH BLESSING BRANCH PURWAKARTA - SITI ROHMAT SITI ROHMAT (POLITEKNIK PIKSI GANESHA, 2018)
The purpose of this study was to determine the effect Excelent Service Loyalty Saving On Mardhatillah BMT Member's Blessing Branch Purwakarta. This research included into descriptive study and using Probability Sampling technique. Data analysis technique used in this research is the validity of the data, the reliability of the data, the normality of the data, the data heterokedastisitas. While the test design using linear regression data analysis, correlation coefficient, coefficient of determination. The results showed that perceptions Service Excelent has a strong connection to the Loyalty Saving On Mardhatillah BMT Member's Blessing Branch Purwakarta. This is evidenced from the results obtained in testing the hypothesis in which the value of 14 121 (t)> 1.66 (t table). With significance level is 0.000 less than 0.05. Correlation coefficient of 0776 as well as the coefficient of determination = 60.2% subsequently acquired the linear regression equation is Y = 2,477 + 0.425 X + e. This means that every 1% increase in Service Excelent then Loyalty Savings will increase by 0425. It can be concluded that the key to the success of BMT Mardhatillah Blessing Branch Purwakarta in reaching and serving the market must apply Service Excelent.